Effects of nutrient enrichment on epipelic diatom assemblages in a nutrient-rich lowland stream, Pampa Region, Argentina - Licursi, Magdalena (2015)
We analyzed the diatom assemblages inhabiting the epipelic biofilm of a Pampean stream, characterized by their high basal nutrient levels, when exposed to a continuous surplus of inorganic nutrients. An in situ experience was conducted, increasing concentrations of N and P in water 3-fold from the basal concentration. Nutrient enrichment was achieved by the use of fertilizer bags distributed along the reach. The period of exposure was of 14 months. The effects of nutrient enrichment were analyzed following a BACIPS ANOVA design. The changes in nutrient concentration were associated with a significant increase in diatom density and a decrease in species richness and diversity. The additional nutrient load also caused the change in the diatom taxa proportion, favoring motile forms, Nitzschia species mainly. The fertilization in La Choza, caused a mild to moderate effect, indeed not immediate, on the diatom assemblage. These delayed responses of moderate intensity could be related with intrinsic characteristics of diatom assemblages pre-adapted to nutrient-rich environments. The rising urbanization and agricultural activity in the Pampean plain, may seriously impair the biodiversity of its rivers if the entrance of nutrients to these ecosystems is not mitigated.